2014
DOI: 10.2217/nnm.14.41
|View full text |Cite
|
Sign up to set email alerts
|

A Vision for Cyclodextrin Nanoparticles in Drug Delivery Systems and Pharmaceutical Applications

Abstract: Cyclodextrins (CDs) have brought a revolution in the pharmaceutical field over the last decade. Natural and modified CDs (α-CD and β-CD) have been studied and some have gained US FDA approval or achieved 'Generally Regarded as Safe' (GRAS) status. Another characteristic of CDs is the ease with which they can be induced to form supramolecular structures for its use in drug delivery. CDs, grafted or crosslinked with polymers, are now being developed into 'smart' systems for efficient targeted drug delivery, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(68 citation statements)
references
References 88 publications
0
68
0
Order By: Relevance
“…Tween 80 was applied to improve the solubility of AMB in PBS and to avoid the adhesion of AMB onto the tube wall. 20 The AMB release from AMBNPs displayed an initial burst of 58.3% in the first 12 days, followed by a slow-release phase sustained for up to 30 days, which was predominantly attributed to the diffusion of AMB. After 30 days, the accumulative AMB release from NPs reached 66.4%, which indicated that the polymer PLGA-TPGS-NPs has favorable drug-release capability.…”
Section: In Vitro Drug Releasementioning
confidence: 93%
See 2 more Smart Citations
“…Tween 80 was applied to improve the solubility of AMB in PBS and to avoid the adhesion of AMB onto the tube wall. 20 The AMB release from AMBNPs displayed an initial burst of 58.3% in the first 12 days, followed by a slow-release phase sustained for up to 30 days, which was predominantly attributed to the diffusion of AMB. After 30 days, the accumulative AMB release from NPs reached 66.4%, which indicated that the polymer PLGA-TPGS-NPs has favorable drug-release capability.…”
Section: In Vitro Drug Releasementioning
confidence: 93%
“…The differences in the antifungal potency and toxicity between free AMB and AMB-NPs may be ascribed to the high stability of AMB-NPs. 20,21 Interestingly, the fungal burden of different organs also favored that both free AMB and AMB-NPs could reduce the amount of bacteria in the lung, kidney, heart, and liver. However, the fungal burden of free AMB-treated mice was significantly higher than that of AMB-NP-treated mice ( Table 3).…”
Section: Therapeutic Efficacy Of Amb-nps In C Albicans Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…181 CDs have been used as a pharmaceutical excipient, mainly to solubilize drugs with poor solubility in an aqueous environment through the synthesis of drug-CD complexes. 182,183 The naturally occurring CDs have been used at a large scale in the evaluation and development of pharmaceutical formulations. However, their applications suffer from certain limitations; for example, β-CD exhibits a restricted solubility in water.…”
Section: Cyclodextrinsmentioning
confidence: 99%
“…CDs have a high level of biocompatibility, are absorbed in the gastrointestinal tract, and are completely metabolized by the colon microflora [6]. Some of them are approved by the Food and Drug Administration or have been accredited as being "generally recognized as safe" (GRAS) [7]. In the cosmetic area, CD performance stands out in the following: solubilize and stabilize specific sensitive components, stabilize emulsions, improve the absorption of active components onto the skin, reduce or eliminate bad aromas from certain components, and reduce the loss of the active components through volatilization, rapid oxidation, destruction by light, etc.…”
Section: Cyclodextrins: General Considerationsmentioning
confidence: 99%